Case Report: Report of a Persian-Speaking Patient with Foreign Accent Syndrome - Robab Teimori; Golnaz Modarresi; Shahla Raghib-Doust; Fereshteh Momeni (University of Social Welfare and Rehabilitation Sciences, 2009)
Foreign Accent Syndrome (FAS) is a rare speech disorder that occurs as a consequence of the left hemisphere lesions. This syndrome is usually manifested by a combination of segmental & suprasegmental deviations in production. Despite the segmental difficulties, prosodic errors often are considered as the main feature of Foreign Accent Syndrome. In this article, we report a case of a fifty three years old Persian - speaker woman who presents, in marked degree, with the characteristic features of FAS as a result of a stroke. To our knowledge, she is the first reported case of this syndrome in Iran. The suprasegmental features of this patient were analyzed by Praat Software (Version 4.1.9.), and were compared with the speech characteristics of Persian normal speakers'. The results, in accordance with the previous findings, confirm major deviations in the prosodic aspects of stress, rate of speech and junctures in the patient's speech